Influences on general practitioner referral to allied health professionals for fall prevention in primary care. (4th June 2019) - Liddle, Jeannine; Clemson, Lindy; Mackenzie, Lynette; Lovarini, Meryl; Tan, Amy; Pit, Sabrina W.; Roberts, Chris; Tiedemann, Anne; Sherrington, Cathie; Willis, Karen
Abstract: Objective: To explore influences on referral for fall prevention from general practitioners (GPs) to allied health professionals (AHPs) to better equip AHPs engage with GPs regarding fall prevention. Methods: Qualitative, semi‐structured interviews with GPs (n = 24), practice nurses (n = 3) and AHPs (n = 15) and field notes were analysed inductively using constant comparative methods. Results: Three main themes regarding influences on GP referral to AHPs for fall prevention were identified as follows: GPs' knowledge of AHPs; The "reliable and good" AHP; and Patient feedback‐Patient choice. Three‐way communication and trust between GP, patient and AHP underpinned each of these themes. Conclusions: Strategies for encouraging GP referral include AHPs personally contacting GPs to explain their services; writing to GPs about every patient seen; and being aware that interprofessional relationships are based on trust and take time to develop. GPs and AHPs are encouraged to communicate directly rather than relying on patients to convey verbal information.